Effectiveness of suicide prevention gatekeeper‐training for university administrative staff in Japan. Issue 1 (4th October 2015) - Hashimoto, Naoki; Suzuki, Yuriko; Kato, Takahiro A.; Fujisawa, Daisuke; Sato, Ryoko; Aoyama‐Uehara, Kumi; Fukasawa, Maiko; Asakura, Satoshi; Kusumi, Ichiro; Otsuka, Kotaro
Abstract : Aims: Suicide is a leading cause of death among Japanese college and university students. Gatekeeper‐training programs have been shown to improve detection and referral of individuals who are at risk of suicide by training non‐mental‐health professional persons. However, no studies have investigated the effectiveness of such programs in university settings in Japan. The aim of this study was to investigate the effectiveness of the gatekeeper‐training program for administrative staff in Japanese universities. Methods: We developed a 2.5‐h gatekeeper‐training program based on the Mental Health First Aid program, which was originally developed for the general public. Seventy‐six administrative staff at Hokkaido University participated in the program. Competence and confidence in managing suicide intervention, behavioral intention as a gatekeeper and attitude while handling suicidal students were measured by a self‐reported questionnaire before, immediately after and a month after the program. Results: We found a significant improvement in competence in the management of suicidal students. We also found improvements in confidence in management of suicidal students and behavioral intention as a gatekeeper after training, though questionnaires for those secondary outcomes were not validated. These improvements continued for a month. About 95% of the participants rated the program as useful or very useful and one‐third of the participants had one or more chances to utilize their skills within a month. Conclusions: The current results suggest the positive effects of the training program in university settings in Japan. Future evaluation that includes comparison with standard didactic trainings and an assessment of long‐term effectiveness are warranted.